2017
DOI: 10.1186/s12872-016-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training significantly increases serum endocan but not osteoprotegerin levels: a prospective observational study

Abstract: AbstractsBackgroundEndocan (EN) was suggested a potential inflammatory and cardiovascular disease (CVD) marker which might also be involved in renal failure and/or renal failure-associated vascular events. It is not clear whether osteoprotegerin (OPG) is a pro- or anti-atherogenic factor, however, it is agreed upon that OPG is elevated in subjects with increased calcification status. The aim of the study was to investigate the influence of long-term physical activity on serum endocan (EN) and osteoprotegerin-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The influence of sports on atherosclerosis [1], inflammation and calcification [2] biomarkers or the lipid profile [3] and its beneficial effect on cardiovascular disease are well-known, and the protective effect of physical activity against the development of malignant diseases is also well established. Recently, a meta-analysis of 126 studies showed that physical activity according to the WHO recommendations leads to a decrease of cancer incidence of 7% for colorectal and breast cancers [4].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of sports on atherosclerosis [1], inflammation and calcification [2] biomarkers or the lipid profile [3] and its beneficial effect on cardiovascular disease are well-known, and the protective effect of physical activity against the development of malignant diseases is also well established. Recently, a meta-analysis of 126 studies showed that physical activity according to the WHO recommendations leads to a decrease of cancer incidence of 7% for colorectal and breast cancers [4].…”
Section: Introductionmentioning
confidence: 99%